Microactuators technologies for biomedical applications - Ahmad Fuaad, Mariatul Rawdhah (Springer Science and Business Media Deutschland GmbH, 2023)
Rapid advancements in technology have facilitated the development of functional micro-electromechanical system (MEMS) actuators. The use of such actuators has recently witnessed a surge in a variety of biomedical applications, owing to their high precision and conformity. This review aims to provide a comprehensive survey of the recently developed MEMS actuators and their use in biomedical applications. In the context of these applications, we discuss the most appropriate and extensively used actuation techniques such as thermo-responsive, magnetic, piezoelectric, and soft actuation. In addition, state-of-the-art biomedical systems, tools, and devices are categorically reviewed with recently utilized actuation techniques, to provide insight into the prospects of implementation. The key parameters responsible for the enhanced performance and efficiency of the actuators were also addressed. Finally, the future research trends in actuation techniques for biomedical applications are discussed.